ER Dynamics and Derangement in Neurological Diseases - Yamanaka, Tomoyuki; Nukina, Nobuyuki (Frontiers in Neuroscience, 2018)
The endoplasmic reticulum (ER) is a morphologically dynamic organelle containing different membrane subdomains with distinct cellular functions. Numerous observations have revealed that ER stress response induced by disturbed ER homeostasis is linked to various neurological/neurodegenerative disorders. In contrast, recent findings unveil that ER structural derangements are linked to the progression of several neurological diseases. These involve two distinct, and likely opposing pathways. One is dysfunction of ER dynamics machinery, leading to disruption of ER network organization. Another one is facilitation of pre-existing machinery, leading to generation of markedly-ordered de novo membranous structure. Restoring the ER network can be the effective way toward the cure of ER-deranged neurological disorders.